Transcription in mosquito hemocytes in response to pathogen exposure - Hillyer, Julián F (BioMed Central, 2009)
Mosquito hemocytes are blood cells that are fundamental for combating systemic infection. A study published in BMC Genomics shows that hemocyte gene transcription in response to immune challenge is pathogen-specific and reaffirms the primary role of these cells in immunity.